Developing Technology-Based Instructional Videos to Enhance Cognitive and Physical Performance in Physical Education - Mary Em Heart C. Zarco; Vivencio L. Calixtro Jr.; Jessica D. Deligero; Alena Mae O. Raymundo; Jonnah Lyn V. Tubac (Bumi Publikasi Nusantara, 2026)
This study developed and evaluated a technology-based instructional video on locomotor and manipulative movements to improve the cognitive and physical performance of Grade VI learners at Tagbilaran City Central Elementary School. Guided by a quasi-experimental pre-test and post-test design, the intervention involved purposively selected learners and was validated by subject experts. The instructional video was assessed on multiple dimensions, including style, creativity, content, music, language, captions, and instructional value, and was rated as outstanding overall. Findings revealed significant improvements in both knowledge and physical skills, demonstrating the effectiveness of instructional videos in fostering comprehension, retention, and performance in Physical Education. While the material was well-received, further refinement in visual organization and inclusivity of language and captions is recommended to ensure broader accessibility. This study underscores the potential of technology-based instructional videos as powerful tools to enhance teaching and learning in Physical Education.